Morphometric Characteristic and Growth Responses of Enhalus acoroides Seedlings Under Different Substrate Composition Treatment - Aditya Hikmat Nugraha; Said Almahdi; Aminatul Zahra; Ita Karlina (Fisheries and Marine Science Faculty - Jenderal Soedirman University, 2021)
Seagrass transplantation in the large-scale requires a large number of seagrass individu from donor ecosystem. This may give negative impact as damage and reducing the number of seagrass in donor ecosystem. One of methods to overcome this case is by developing transplants using seagrass nut as source for seed. Substrate is one of factors that influence the growth of seagrass. The aim of this study was to compare the effect of differences in substrate composition on morphologi and growth of Enhalus acoroides seeds. Observations were carried out by treatment using mud, sand and mixed substrates sand with mud. The survival rate of Enhalus acoroides seeds was quite high of 100% but it had a lower value of 93.30% on sand substrate. The longest leaf is on the mud substrate with a length of 5.9 cm, the leaf width has the same size in each substrate with a value of 0.4 cm, the highest number of leaves were found in the sand and mixture substrate with 5 strands, the longest root size was in the mixed substrate with a length of 5 cm. The growth of Enhalus acoroides seagrass seeds did not show any significant difference. The highest growth was found in the mud substrate with a value of 0.10 cm/day. Keywords: Enhalus acoroides, seagrass,seed, substrate, transplantation